BIOMEDICAL TECHNOLOGY, ETHICS AND CRIMINAL LAW - Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The paper analyzes a complex relationship between biomedical technology and ethics and offers insight into the role of the criminal law in regulating this subject matter. In the first part of the paper the author offers analysis of the relationship between medicine and ethics as well as the ethical rules of conduct in modern medicine and stresses the need for legal intervention in this matter. In the second part of the paper the author points out that sudden development of biomedicine and biotechnology in the last twenty years has led the society into a great temptation and forced onto the ethics and the law considerable challenges. While discussing the relationship between biotechnology and ethics, the author pointed out that it would be more suitable to declare the principle of tolerance, kept in check by the principle of responsibility, to be a fundamental principle in biotechnology. However, traditional principle of ethics in medicine should not all together be disregarded. In the last part of the paper the author offers analysis of the extent and perspective of the criminal law reaction in the subject matter and concludes that in the field of biotechnology not too much hope should rest on the role of the criminal law.